ADVANCES IN CANNABINOID-BASED PAIN MANAGEMENT: EFFICACY AND EVIDENCE - Michael Platschek; Maksym Sikora; Jakub Nowak; Michał Drabik; Klaudia Dybalska; Julia Kosmulska; Mateusz Kęska; Anna Barbara Tuleja; Sylwia Wiktoria Kolano; Karol Józef Szkarłat (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Chronic pain is a significant global health challenge, and its management is complicated by the substantial risks associated with conventional therapies such as opioids. Cannabinoids, targeting the endocannabinoid system, have been developed as effective therapeutic options. This systematic review assesses current research evidence about cannabinoid safety and effectiveness for managing various chronic pain conditions to establish their worth in modern pain management. Main Findings: The evidence for cannabinoid efficacy is highly condition-specific. Moderate-quality evidence supports cannabinoid-based medicines for chronic neuropathic pain, demonstrating reduced pain intensity and improved sleep. The strongest evidence exists for spasticity-related pain in multiple sclerosis, for which nabiximols is an approved treatment. Key guidelines recommend that cannabinoids have no efficacy for cancer pain. There is currently no clinical evidence for providing relief of inflammatory pain, such as fibromyalgia. Evidence also supports an adjuvant role via a potential "opioid-sparing" effect. The safety profile includes moderate side effects, which include dizziness and somnolence, and does not carry the lethal respiratory depression risk associated with opioids. Conclusion: Cannabinoids provide a new pharmacological approach, but they do not work as a universal analgesic. The existing evidence supports their utility as adjunctive therapy for certain, refractory conditions — especially neuropathic pain and MS-related spasticity. Compared to opioids, their favorable safety profile would indicate they could represent an important adjunct for multimodal pain management. More large-scale trials using standardized formulations are required to specify their exact place they hold in evidence-based care.